Más y mejores conflictos en Uruguay. Políticas de gobierno y autonomía de los trabajadores - Luis Ibarra (Revista Enfoques, 2011)
The regulation of wages was at the center of a growing number of labor disputes in Uruguay. The article analyzes changes in government policy as a response to institutional tensions and charts how struggles have fared. The paper shows the way in which conflicts have led to outcomes that not only contradict the government’s guidelines but also express a tendency among workers toward political autonomy.